Effects of structural modifications on the photosensitizing properties of dialkylcarbocyanine dyes in homogeneous and heterogeneous solutions - Krieg, Marianne; Bilitz, James M.; Srichai, Monvadi B.; Redmond, Robert W. (Biochimica et biophysica acta, 1994)
The photophysical characterization of structurally modified symmetric dialkylthiacarbocyanine dyes in homogenous and biomimetic media is reported. The aim of the two specific structural modifications was to increase singlet oxygen production, hence enhancing the photosensitizing properties of these cyanine dyes. Specifically, (1) the sulfur was exchanged with selenium in order to enhance intersystem crossing via an internal heavy atom effect and (2) substituents of differing size were introduced into the meso-position of the polymethine chain to reduce photoisomerization. The result of incorporation of an internal heavy atom (selenium) into the structure of the dye yields the expected effect: this modification results in a 22-fold increase in the rate of intersystem crossing, but does not change the remaining competing deactivation rates of teh first excited single state. As a consequence, singlet oxygen quantum yields increase from 0.001 to 0.014 in ethanol and from 0.006 to 0.08 in unilamellar liposomes. In the case of the meso-substituted thiacarbocyanine dyes, a significant reduction in photoisomerization is indeed observed. However, this modification drastically enhances internal conversion which then becomes the main deactivation pathway of the first excited singlet state. As a result, very small fluorescence and singlet oxygen quantum yields are obtained, e.g. 0.006 and 0.001, respectively, in ethanol.